2010
DOI: 10.1111/j.1564-913x.2010.00089.x
|View full text |Cite
|
Sign up to set email alerts
|

On‐the‐job training in Europe: Determinants and wage returns

Abstract: Using data from the European Community Household Panel on six countries over the period 1995-2001, this article investigates the determinants of workers' participation in training activities and the effects of training on wages. Based on measures of four distinct training types, the authors find that while OLS estimates yield significant wage returns to training for nearly all of the countries, fixed-effects estimations show returns to be not statistically different from zero. This suggests that wage returns t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
0
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(94 citation statements)
references
References 40 publications
(36 reference statements)
3
81
0
10
Order By: Relevance
“…As Fritsche (2012) shows, in the case of Germany, the probability of receiving training increases with age up to a certain level after which it decreases (the effect appears as an inverted U-shape in a graph). Even so, in some studies for some European countries, age only has a statistically significant effect for men (Arulampalam et al, 2004;Booth, 1991;Albert et al, 2010). In addition, Drewes (2008) indicates that in Canada participation in training programmes falls sharply with age except when the training is related directly to the job, in which case the effect of age is more even.…”
Section: Personal Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…As Fritsche (2012) shows, in the case of Germany, the probability of receiving training increases with age up to a certain level after which it decreases (the effect appears as an inverted U-shape in a graph). Even so, in some studies for some European countries, age only has a statistically significant effect for men (Arulampalam et al, 2004;Booth, 1991;Albert et al, 2010). In addition, Drewes (2008) indicates that in Canada participation in training programmes falls sharply with age except when the training is related directly to the job, in which case the effect of age is more even.…”
Section: Personal Variablesmentioning
confidence: 99%
“…In the United Kingdom, Albert et al (2010) indicate that working in the industrial sector favors training, while in almost all the European countries analyzed working in the financial sector has a positive effect. On the contrary, the effect is negative if the firm is in the construction sector.…”
Section: Characteristics Of the Firmmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown that participation in further training is highly selective and widely depends on individual and work-related factors (see, for example, Albert, García-Serrano, & Hernanz, 2010;Kyndt & Baert, 2013). Although less explored, also family-related factors such as the presence of a partner, children, or economic hardship can be assumed to influence the individual's probability to train (Chan & Auster, 2003;Sussman, 2002): further training can be expensive and time-consuming and therefore less attractive to some employees because of their family responsibilities.…”
Section: Fors Switzerlandmentioning
confidence: 99%
“…Furthermore, Acemoglu and Zilibotti (2001) show that even when all countries have access to the same set of technologies, there will be large cross-country productivity differences on account of technology-skill mismatch. 2 In this paper, therefore, we take information on training activities for 21 European countries, largely disaggregated across 16 economic sectors, and use it to explore whether continuous vocational training is a relevant driving force of productivity growth. To conduct this analysis we recall Jones (1997), and extend the basic Solow model by including the possibility of skills accumulation by way of job related training at the sectoral level.…”
Section: Introductionmentioning
confidence: 99%